Lignocellulose and fluorescent powder synergistic light response transparent light-emitting film and preparation and recycling method thereof

The single-phase transparent luminescent wood film is designed through the collaborative light response of cellulose and phosphors, which solves the problems of color unevenness, toxicity and non-recyclability in the application of existing transparent luminescent wood, and achieves a highly integrated and recyclable Warm white light emission, suitable for a variety of applications.

CN119304976APending Publication Date: 2025-01-14CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411665848.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the application of existing transparent luminescent wood, there are problems such as the combination of multiphase luminescent materials that lead to color unevenness, the toxicity of some luminescent materials and the inability to recover and reuse of packaging materials, which hinders its w-LED, optical temperature measurement sensing and Practical applications in the fields of plant lighting and other fields.

Method used

By utilizing the synergistic light response of cellulose and inorganic commercial phosphors, a single-phase transparent luminescent wood film was designed. The wood film uses lignocellulose as the blue light emission center and the phosphor as the red light emission center to achieve white light emission and Recycling in aqueous solutions through the water-soluble properties of polyvinyl alcohol.

Benefits of technology

It achieves the warm white light emission of a single-phase film, has a high degree of integration, avoids the packaging and combination problems of multi-phase luminescent materials, is recyclable, and is suitable for fields such as w-LED, optical temperature sensing, and plant lighting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119304976A_ABST
    Figure CN119304976A_ABST
Patent Text Reader

Abstract

The invention aims to realize reutilization of optical illumination based on lignocellulose natural fluorescence emission, and discloses a preparation method of a novel full-spectrum emission color-adjustable recyclable flexible transparent luminous wood film. Wood is soaked in a delignification solution to remove light absorption lignin to obtain a delignified wood frame, then a mixed homogeneous solution containing PVA and red commercial powder is subjected to vacuum infiltration into a white delignified wood support, and the transparent luminous wood is prepared. Transparent light-emitting wood shows white light emission based on synergistic light response of lignocellulose (blue light emission) and fluorescent powder (red light emission) under 365nm ultraviolet excitation. The transparent light-emitting wood film disclosed by the invention is used as a potential substitute of a petroleum-based packaging material in the field of light-emitting illumination, can be recycled in an aqueous solution, is applied to the fields of plant illumination, white light LEDs, non-contact temperature sensing and the like, and provides a new theoretical thought for green optical functionalization treatment of wood.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of novel recyclable luminous wood, and in particular relates to a recyclable flexible luminous film based on blue light emission of wood cellulose and red commercial powder-tuned full-spectrum emission and a preparation method thereof. Background Art

[0002] In recent years, with the scarcity of fossil energy and the increasingly serious global warming, the development of a new generation of low-carbon, green, energy-saving, environmentally friendly and recyclable bio-based materials has become an inevitable trend for global economic and sustainable development. Among them, wood is recognized as an excellent bio-based material because of its wide source, low price and environmental sustainability. In recent years, by utilizing the multi-scale hierarchical and mesoporous structure of wood, its structure and composition can be modified at the micron and nanoscale by physical and chemical methods to obtain functional wood, which can be applied to green electronics, energy storage, biosensing and optical lighting. Among them, transparent luminous wood has developed rapidly in the field of optical lighting due to its high anisotropy, high transmittance and haze, low thermal conductivity and excellent mechanical properties. At present, the main research direction is to achieve white light emission by incorporating luminescent materials of various colors (such as quantum dots, carbon dots, etc.) to promote its application in w-LED. However, the combination of multi-phase luminescent materials will lead to new problems. For example, different colors of phosphors have different attenuation rates, which will affect the color unevenness of the packaged device; some luminescent materials are toxic; the packaging materials of multi-phase phosphors are petroleum-based materials that cannot be recycled and reused, which puts pressure on resources and the environment. These problems will hinder the practical application of transparent luminous wood.

[0003] Cellulose is a water-insoluble, low-cost polysaccharide and the main structural component of wood. The long cellulose chain does not contain π units, but is rich in O atoms, in which the electron-rich oxygen atoms are closely aggregated through spatial conjugation to produce "aggregated chromophores" with rich energy levels and low energy gaps. The interaction between oxygen atoms helps to solidify the conformation of the clusters. In addition, the abundant hydrogen bonds are also conducive to the reasonable solidification of the conformation, which is conducive to radiation emission. The aggregation of oxygen atoms and conformational hardening make cellulose have broadband blue light emission under ultraviolet light. In addition, polyvinyl alcohol has excellent water solubility, biocompatibility and degradability, contains a large number of hydroxyl groups in the molecular chain, has good film-forming ability and recyclability, and has a low impact on the environment.

[0004] Therefore, in existing applications, there is an urgent need to design and manufacture integrated single-phase innovative multifunctional fluorescent films with special properties such as adjustable luminescence performance, flexibility, biodegradability and recyclability. Summary of the invention

[0005] The purpose of the present invention is to provide a new flexible transparent luminescent film with adjustable full-spectrum emission color and a preparation method based on the broadband blue fluorescence emission phenomenon of natural wood cellulose, so as to overcome the shortcomings of the prior art. The method uses the synergistic light response of cellulose and inorganic commercial phosphors to give the single-phase transparent luminescent wood film the ability to emit white light. Due to the property that PVA is easily soluble in water, the luminescent wood film can be recycled in aqueous solution, realizing the development of recyclable packaging and integrated luminescent materials, and has broad application prospects in w-LED, optical temperature sensing, plant lighting, etc.

[0006] The present invention discloses a transparent luminescent film with synergistic light response of wood cellulose and phosphor and a preparation method thereof, comprising the following steps: (1) using rotary cutting technology to obtain a wood chip template and drying it for later use; (2) dissolving sodium chlorite in deionized water and stirring evenly, adding glacial acetic acid to adjust the pH to 4.6 to prepare a delignification solution, treating the wood chip template dried in step (1) with the delignification solution, heating it to 80° C. and keeping it warm for 3 hours until the sample turns white, and then rinsing it in deionized water for 3 times to remove residual chemicals; (3) freeze-drying the sample obtained in step (2) to obtain a delignified wood template for further use; (4) dissolving polyvinyl alcohol (PVA) in deionized water and heating the solution to 90° C. to obtain a polymer solution; (5) CaAlSiN:Eu containing rare earth ions 2+ The red fluorescent powder is added to the polymer solution obtained in step (4) and subjected to ultrasonic dispersion treatment using a cell crusher to obtain a uniform fluorescent mixed solution; (6) Immerse the delignified wood template obtained in step (3) in a plastic box containing a fluorescent mixed solution and place it in a vacuum drying oven. Vacuum immerse it for 1.5 hours at room temperature until the mixed solution is fully immersed and there are no bubbles. Then cure it in an oven at 60° C. for about 12 hours to obtain a transparent luminous wood film.

[0007] Preferably, the wood sample obtained in step (1) is basswood, and the wood chips obtained by rotary cutting have a thickness of about 200 μm, a density of 0.5 g / cm3, and a sample size of about 80 mm×30 mm×0.2 mm.

[0008] Preferably, the mass volume ratio of sodium chlorite, glacial acetic acid and deionized water in the delignification solution obtained in step (2) is 5:2:98, and the concentration of the sodium chlorite solution is 4.8wt%.

[0009] Preferably, the sample in step (3) is freeze-dried at -60°C for 12 hours to ensure that the pore structure of the wood remains intact.

[0010] Preferably, the concentration of the polyvinyl alcohol solution in step (4) is 8 wt %, the polyvinyl alcohol is 1788 low viscosity type, and the alcoholysis degree is 87.0-89.0%.

[0011] Preferably, the red phosphor in step (5) is commercially available CaAlSiN:Eu 2+ Commercial powder, wherein PVA solution (8wt%) and CaAlSiN:Eu 2+ The mass ratio of is 1000:1-6, and the polymer solution is ultrasonically treated with a cell crusher at 60% power for 15 min to ensure thorough dispersion.

[0012] Preferably, in step (6), the depth of the fluorescent mixed solution into which the delignified wood template is immersed is 15 times the thickness of the delignified wood template, which is about 3 mm, and the vacuum degree of the vacuum impregnation is 133 Pa.

[0013] The present invention also provides a transparent luminescent wood film prepared by the transparent luminescent film having a synergistic light response of wood cellulose and fluorescent powder as described above and a preparation method thereof.

[0014] The present invention also provides a method for recycling the above-mentioned recyclable transparent luminous film, and the steps are as follows: (1) immersing the transparent luminescent film in a degradation solution for 12 hours, and then subjecting it to ultrasonic treatment to depolymerize and dissolve the polyvinyl alcohol, thereby obtaining a uniform mixed solution of polyvinyl alcohol and phosphor and a delignified wood template; (2) The recovered delignified wood template is washed and freeze-dried, and the mixed recovery liquid of polyvinyl alcohol and phosphor can be directly used for the preparation of new transparent luminescent film without separation, thus achieving recyclability.

[0015] Preferably, in step (1), the degradation solution obtained in step (1) is deionized water.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The present invention uses wood cellulose as the blue light emission center and phosphor as the red light emission center to achieve warm white light emission of a single-phase thin film through synergistic light response. It can be directly packaged with an ultraviolet chip into a w-LED, with a high degree of integration. There is no need to consider the impact of the packaging combination of multi-phase luminescent materials on the luminescent performance of the device; at the same time, the warm white light emission of the device can effectively alleviate the current blue light pollution. 2. The present invention uses the delignified wood formwork with various anisotropies as the structural frame to provide a uniform lighting environment. 3. The transparent luminescent wood film prepared by the present invention is dual-wavelength emitting. The blue light of cellulose is more sensitive to temperature changes and has a completely different thermal response spectral signal compared to red light. It can be applied to the field of non-contact temperature measurement through fluorescence intensity ratio (FIR) technology, and has the advantages of no contact, rapid detection of moving objects and high sensitivity. 4. The dual emission bands of the transparent luminescent wood film prepared by the present invention overlap well with the absorption bands of 400-500nm and 600-700nm required for plant growth illumination and can be applied to a plant growth optical platform. 5. The preparation process of PVA composite delignified wood template is simple and can be recycled repeatedly based on its water-soluble characteristics.

[0018] The above content is an overview of the technical solution. The present invention will be further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to clearly illustrate the technical solutions for implementing the present invention, the implementation process and the drawings required for use in the embodiments are briefly introduced below. The following drawings only show some embodiments of the present invention and therefore should not be regarded as limiting the present invention in any form. Figure 1 It is a schematic diagram of a transparent luminescent film with synergistic light response of wood cellulose and phosphor and a preparation method thereof of the present invention; Figure 2 This is a diagram of the optical performance of the transparent fluorescent film of Example 1 of the present invention; Figure 3 The recovered samples and process images of Example 1 of the present invention; Figure 4 This is a diagram of the optical performance of the transparent fluorescent film of Example 2 of the present invention; Figure 5 This is a diagram of the optical performance of the transparent fluorescent film of Example 3 of the present invention; Figure 6 The recovered samples and process images of Example 3 of the present invention; Figure 7 The recycled and reused sample and spectrum of Example 3 of the present invention; DETAILED DESCRIPTION In order to better understand the technical content of the present invention, the technical solution of the present invention is further described below in conjunction with specific embodiments and drawings. It should be understood that the embodiments of the present invention are only used to illustrate the present invention and are not intended to limit the present invention in any form. Example 1 A transparent luminescent film with synergistic light response of wood cellulose and phosphor and a preparation method thereof, comprising the following steps: (1) The basswood was cut by rotary cutting technology to obtain wood chips with a thickness of about 200 μm, and the sample size was cut into a size of about 80 mm × 30 mm × 0.2 mm. The density of the sample after drying was 0.5 g / cm3; (2) Weigh 25 g of sodium chlorite and dissolve it in 490 ml of deionized water and stir it to a concentration of 4.8 wt %. Then, add 10 ml of glacial acetic acid to the sodium chlorite solution to adjust the pH value to 4.6 to obtain a delignified solution. Immerse the dried wood chip template in step (1) in the delignified solution and heat it at 80° C. for 3 h to perform delignification treatment until the sample appears white. (3) Take out the sample obtained in step (2) and rinse it in deionized water for 3 times to remove residual chemicals and freeze-dry it at -60° C. for 12 h to obtain a delignified wood template. (4) Weighing 40 g of polyvinyl alcohol and dissolving it in 460 ml of deionized water at 90° C. to prepare a polymer solution with a concentration of 8 wt %; (5) Immersing the delignified wood template prepared in step (3) into a plastic box containing the polymer solution prepared in step (4), wherein the depth of the solution is 15 times the thickness of the delignified wood template, which is about 3 mm, and placing it in a vacuum drying oven, vacuum impregnating it at room temperature for 1.5 hours, and the vacuum degree of the vacuum impregnation is 133 Pa. After the mixed solution is fully impregnated and no bubbles are present, it is then cured in an oven at 60° C. for about 12 hours to obtain a transparent luminous wood film; A method for recycling a transparent luminescent film with synergistic light response of wood cellulose and phosphor comprises the following steps: (1) immersing a transparent luminescent film of 15 mm × 25 mm × 0.2 mm in a 50 ml aqueous solution at room temperature for 12 h, and performing ultrasonic treatment to depolymerize and dissolve the polyvinyl alcohol, thereby obtaining a uniform polyvinyl alcohol solution and a delignified wood template; (2) The recovered delignified wood template is washed and freeze-dried at -60°C for 12 h. The recovered polyvinyl alcohol liquid can be directly used for the preparation of new transparent luminescent film without separation. After testing, the optical properties of the transparent luminous wood film prepared in this embodiment are as follows: Figure 2 shown. Figure 2 (a) shows that Example 1 is placed on a background with letters printed on it, and it can be seen that it has good transparency under visible light, with a transmittance of about 82%. Figure 2 (b) shows a fluorescent photograph of the transparent luminous wood film of Example 1 under ultraviolet light. Figure 2 (c) shows the PL spectrum of Example 1. Its full width at half maximum (FWHM) is 120 nm, which is attributed to wood cellulose, indicating blue light emission visible to the naked eye. The corresponding CIE chromaticity diagram is as follows: Figure 2(d) shows that its coordinates are (0.206 0.241). The recovery system of Example 1 is as follows Figure 3 As shown, Figure 3 (a) is the image of Example 1 before and after being placed in the dissolving solution under room light and ultraviolet light, respectively. Figure 3 (b) Images of the recovered solvent and the recovered delignified wood template under room light and UV illumination, respectively. Example 2 A transparent luminescent film with synergistic light response of wood cellulose and phosphor and a preparation method thereof, comprising the following steps: (1) The basswood was cut by rotary cutting technology to obtain wood chips with a thickness of about 200 μm, and the sample size was cut into a size of about 80 mm × 30 mm × 0.2 mm. The density of the sample after drying was 0.5 g / cm3; (2) Weigh 25 g of sodium chlorite and dissolve it in 490 ml of deionized water and stir it to a concentration of 4.8 wt %. Then, add 10 ml of glacial acetic acid to the sodium chlorite solution to adjust the pH value to 4.6 to obtain a delignified solution. Immerse the dried wood chip template in step (1) in the delignified solution and heat it at 80° C. for 3 h to perform delignification treatment until the sample appears white. (3) Take out the sample obtained in step (2) and rinse it in deionized water for 3 times to remove residual chemicals and freeze-dry it at -60° C. for 12 h to obtain a delignified wood template. (4) Weighing 40 g of polyvinyl alcohol and dissolving it in 460 ml of deionized water at 90° C. to prepare a polymer solution with a concentration of 8 wt %; (5) Commercially available CaAlSiN:Eu containing rare earth ions 2+ Red phosphor is made of PVA and CaAlSiN:Eu 2+ The mass ratio of 1000:4 is added to the polymer solution obtained in step (4) and ultrasonically dispersed using a cell crusher to obtain a uniform fluorescent mixed solution; (6) the delignified wood template obtained in step (3) is immersed in a plastic box containing the fluorescent mixed solution obtained in step (5), the solution depth is 15 times the thickness of the delignified wood template, about 3 mm, and the template is placed in a vacuum drying oven, vacuum impregnated for 1.5 hours at room temperature, the vacuum degree of the vacuum impregnation is 133 Pa, and the mixed solution is fully impregnated and no bubbles are present, and then cured in an oven at 60°C for about 12 hours to obtain a transparent luminous wood film; After testing, the optical properties of the transparent luminous wood film prepared in this embodiment are as follows: Figure 4 shown. Figure 4 (a) shows that Example 2 is placed on a background with letters printed on it, and it can be seen that it has good transparency under visible light, with a transmittance of about 80%. Figure 4(b) shows a fluorescent photograph of the transparent luminous wood film of Example 2 under ultraviolet light. Figure 4 (c) shows the PL spectrum of Example 2, indicating white light emission visible to the naked eye. The corresponding CIE chromaticity diagram is as follows: Figure 4 As shown in (d), its coordinates are (0.342 0.323). Example 3 A transparent luminescent film with synergistic light response of wood cellulose and phosphor and a preparation method thereof, comprising the following steps: (1) The basswood was cut by rotary cutting technology to obtain wood chips with a thickness of about 200 μm, and the sample size was cut into a size of about 80 mm × 30 mm × 0.2 mm. The density of the sample after drying was 0.5 g / cm3; (2) Weigh 25 g of sodium chlorite and dissolve it in 490 ml of deionized water and stir it to a concentration of 4.8 wt %. Then, add 10 ml of glacial acetic acid to the sodium chlorite solution to adjust the pH value to 4.6 to obtain a delignified solution. Immerse the dried wood chip template in step (1) in the delignified solution and heat it at 80° C. for 3 h to perform delignification treatment until the sample appears white. (3) Take out the sample obtained in step (2) and rinse it in deionized water for 3 times to remove residual chemicals and freeze-dry it at -60° C. for 12 h to obtain a delignified wood template. (4) Weighing 40 g of polyvinyl alcohol and dissolving it in 460 ml of deionized water at 90° C. to prepare a polymer solution with a concentration of 8 wt %; (5) Commercially available CaAlSiN:Eu containing rare earth ions 2+ Red phosphor is made of PVA and CaAlSiN:Eu 2+ The mass ratio of 1000:6 is added to the polymer solution obtained in step (4), and ultrasonic dispersion is performed using a cell crusher to obtain a uniform fluorescent mixed solution; (6) the delignified wood template obtained in step (3) is immersed in a plastic box containing the fluorescent mixed solution obtained in step (5), the solution depth is 15 times the thickness of the delignified wood template, about 3 mm, and the template is placed in a vacuum drying oven, and vacuum impregnated for 1.5 hours at room temperature, the vacuum degree of the vacuum impregnation is 133 Pa, and the mixed solution is fully impregnated and no bubbles are present, and then cured in an oven at 60°C for about 12 hours to obtain a transparent luminous wood film; A method for recycling a transparent luminescent film with synergistic light response of wood cellulose and phosphor comprises the following steps: (1) A transparent luminescent film of 15 mm × 25 mm × 0.2 mm size was immersed in 50 ml of aqueous solution at room temperature for 12 h, and ultrasonic treatment was performed to depolymerize and dissolve the polyvinyl alcohol to obtain a uniform mixed solution of polyvinyl alcohol and phosphor and a delignified wood template; (2) The recovered delignified wood template is washed and freeze-dried at -60°C for 12 hours. The mixed recovery liquid of polyvinyl alcohol and phosphor can be directly used for the preparation of new transparent luminescent film without separation. After testing, the optical properties of the transparent luminous wood film prepared in this embodiment are as follows: Figure 5 shown. Figure 5 (a) shows that Example 3 is placed on a background with letters printed on it, and it can be seen that it has good transparency under visible light, with a transmittance of about 77%. Figure 5 (b) shows a fluorescent photograph of the transparent luminous wood film of Example 3 under ultraviolet light. Figure 5 (c) shows the PL spectrum of Example 3, indicating red light emission visible to the naked eye. The corresponding CIE chromaticity diagram is as follows: Figure 5 (d) shows that its coordinates are (0.405 0.312). The recovery system of Example 3 is as follows Figure 6 As shown, Figure 6 (a) is the image of Example 3 before and after being placed in the dissolving solution under room light and ultraviolet irradiation, respectively. Figure 6 (b) Images of the recycled PVA and phosphor solution and the recycled delignified wood template under room light and UV irradiation, respectively. Figure 7 (a) is a room light and fluorescent photograph of a recycled transparent luminescent wood film obtained by re-filtration using the recycled solution of Example 3 and the recycled delignified wood template. Figure 7 (b) The PL spectrum of the recycled transparent luminescent wood film shows red light emission visible to the naked eye, which is consistent with the fluorescence properties of the sample before recycling.

Claims

1. A transparent luminescent film with synergistic light response of wood cellulose and phosphor and a method for preparing and recycling the film, characterized in that: The steps include: (1) using rotary cutting technology to obtain a wood chip template and drying it for later use; (2) dissolving sodium chlorite in deionized water and stirring evenly, adding glacial acetic acid to adjust the pH to 4.6 to prepare a delignification solution, treating the wood chip template dried in step (1) with the delignification solution, heating it to 80° C. and keeping it warm for 3 hours until the sample turns white, and then rinsing it in deionized water for 3 times to remove residual chemicals; (3) freeze-drying the sample obtained in step (2) to obtain a delignified wood template for further use; (4) dissolving polyvinyl alcohol (PVA) in deionized water and heating the solution to 90° C. to obtain a polymer solution; (5) CaAlSiN:Eu containing rare earth ions 2+ The red fluorescent powder is added to the polymer solution obtained in step (4) and subjected to ultrasonic dispersion treatment using a cell crusher to obtain a uniform fluorescent mixed solution; (6) Immersing the delignified wood template obtained in step (3) into a plastic box containing a fluorescent mixed solution and placing it in a vacuum drying oven, vacuum impregnating at room temperature until the mixed solution is fully impregnated and no bubbles are present, then curing in an oven at 60° C. for about 12 hours to obtain a recyclable transparent luminous wood film.

2. The transparent luminescent film with synergistic light response of wood cellulose and phosphor and the preparation method thereof according to claim 1, characterized in that: The wood sample obtained in step (1) is basswood, and the wood chips obtained by rotary cutting have a thickness of about 200 μm, a density of 0.5 g / cm3, and a sample size of about 80 mm×30 mm×0.2 mm.

3. The transparent luminescent film with synergistic light response of wood cellulose and phosphor and the preparation method thereof according to claim 1, characterized in that: The mass volume ratio of sodium chlorite, glacial acetic acid and deionized water in the delignification solution obtained in step (2) is 5:2:98, and the concentration of the sodium chlorite solution is 4.8wt%.

4. The transparent luminescent film with synergistic light response of wood cellulose and phosphor and the preparation method thereof according to claim 1, characterized in that: The concentration of the polyvinyl alcohol solution in step (4) is 8 wt %, and the polyvinyl alcohol is 1788 low-viscosity type with a degree of alcoholysis of 87.0-89.0%.

5. The transparent luminescent film with synergistic light response of wood cellulose and phosphor and the preparation method thereof according to claim 1, characterized in that: The red phosphor in step (5) is commercially available CaAlSiN:Eu 2+ Commercial powder, wherein PVA solution (8wt%) and CaAlSiN:Eu 2+ The mass ratio of is 1000:1-6, and the polymer solution is ultrasonically treated with a cell crusher at 60% power for 15 min to ensure thorough dispersion.

6. The transparent luminescent film with synergistic light response of wood cellulose and phosphor and the preparation method thereof according to claim 1, characterized in that: In step (6), the depth of the fluorescent mixed solution immersed in the delignified wood template is 15 times the thickness of the delignified wood template, which is about 3 mm, and the vacuum degree of vacuum impregnation is 133 Pa.

7. A recyclable transparent luminescent film prepared according to the method according to any one of claims 1 to 6.

8. The method for recycling the transparent luminescent film with synergistic light response of wood cellulose and phosphor according to claim 7, comprising the following steps: (1) immersing the transparent luminescent film in a degradation solution for 12 hours, and then subjecting it to ultrasonic treatment to depolymerize and dissolve the polyvinyl alcohol, thereby obtaining a uniform mixed solution of polyvinyl alcohol and phosphor and a delignified wood template; (2) The recovered delignified wood template is washed and freeze-dried, and the mixed recovery liquid of polyvinyl alcohol and phosphor can be directly used for the preparation of new transparent luminescent film without separation, thus achieving recyclability.

9. The transparent luminescent film with synergistic light response of wood cellulose and phosphor as claimed in claim 8 and the preparation and recycling method thereof, characterized in that: The degradation solution obtained in step (1) is deionized water.